(untitled) - Rufer-Bach, Kimberly (Indianapolis, Ind., 2009)
Business is booming in Second Life, and many residents are earning big bucks in-world—and so can you. This unique guide walks you through what it takes to launch and run a successful Second Life business. Packed with insider tips from some of the metaverse’s best-known entrepreneurs, it delivers the lowdown on SL business basics and shows you step by step how to succeed in popular business niches, from real estate and construction to fashion, gadgets, toys, entertainment, music, blogging and more.
Keywords: Second Life (Game),Shared virtual environments,Trò chơi,Chia sẽ môi trường ảo; Social aspects,Khía cạnh xã hội